Social disconnectedness among widows in Nigeria: probing the effects of self-monitoring intervention - Moses, Victor (The European Research Journal, 2019)
Objectives: There could be no group more affected by social disconnectedness than widows and many who suffer from social disconnectedness live a lonely life, suffer depression, anxiety, low self-esteem and self-worth, and are hunted by the constant thought of suicide. Developing an intervention to provide reprieve may help widows take back their lives. This article therefore, presents the results of a study probing the effectiveness of self-monitoring intervention in reducing social disconnectedness among the widows in Kaduna state, Nigeria.Methods: The study used the quasi-experimental method involving pretest and posttest. The data were collected using Social Disconnectedness Questionnaire from 47 widows in the treatment group and 45 widows in the waitlist control group. The mean age of the participants (42.33 ± 6.38 years [95%CI = 41.02-43.63], range; 28.0-56.0 years).Results: Analysis of the data suggests that self-monitoring intervention is significantly effective in reducing social disconnectedness behaviour problem among the widows in the study area. After eight weeks of self-monitoring intrevention, social disconnectedness behaviour among the widows reduced by 39% compared to 5.63% observed in the waitlist control group. Conclusions: The outcome adds to the literature as one of few studies investigating self-monitoring intervention among widows and calls for increased probing to establish the efficacy of self-monitoring in reducing social disconnectedness in widows in Nigeria and elsewhere in the world.